2014
DOI: 10.3171/2014.2.peds13493
|View full text |Cite
|
Sign up to set email alerts
|

Return to system within 30 days of discharge following pediatric shunt surgery

Abstract: Object The rate of readmission after CSF shunt surgery is significant and has caught the attention of purchasers of health care. However, a detailed description of clinical scenarios that lead to readmissions and reoperations after index shunt surgery is lacking in the medical literature. Methods This study included 1755 shunt revision and insertion surgeries that were performed at a single institution b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 20 publications
2
32
0
Order By: Relevance
“…This finding matches the finding from our previously conducted shunt readmission study, 3 thereby confirming that after-hours surgery is a promising factor for future study (Table 4). It is crucial to point out that procedure start time is only a surrogate marker (similar to hospital LOS).…”
Section: Comparing Results Of Shunt and Non-shunt Surgeriessupporting
confidence: 89%
See 1 more Smart Citation
“…This finding matches the finding from our previously conducted shunt readmission study, 3 thereby confirming that after-hours surgery is a promising factor for future study (Table 4). It is crucial to point out that procedure start time is only a surrogate marker (similar to hospital LOS).…”
Section: Comparing Results Of Shunt and Non-shunt Surgeriessupporting
confidence: 89%
“…Previously we had documented the strong relationship between shunt surgery itself and early patient readmissions. 3,14 This correlation, while vital to a complete apprehension of factors driving early readmission after all pediatric neurosurgical procedures, is a powerful confounder in statistical models. Carefully teasing the impact of shunt surgery apart from non-shunt neurosurgical procedures allows for a clearer analysis of clinical factors that are not shunt related.…”
Section: 15mentioning
confidence: 99%
“…To our knowledge, this is the first study in which the NSQIP database has been used to examine rates and risk factors for readmission after pediatric neurosurgery. While previous studies have reported return to system after pediatric neurosurgery at single institutions 9,21,26 or after pediatric shunt surgery, 20 the statistical power of a large national patient sample may provide a more representative picture of readmission outcomes for general pediatric neurosurgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric neurosurgery had the highest morbidity and mortality rates of any pediatric surgical specialty in a beta phase report of the American College of Surgeons (ACS) National Surgical Quality Improvement Programā€“Pediatric (NSQIP-P) database, indicating a need to assess patient risk factors for complications, readmission, and other outcome measures in neurosurgery. 4 Previous studies have investigated return to system (readmission or reoperation) after pediatric neurosurgery at a single institution 9,21,26 and 30-day outcomes after pediatric shunt surgery; 20 to our knowledge, however, no study has used a national, multiinstitutional patient database with follow-up to analyze risk factors for readmission after any pediatric neurosurgical procedure. Identifying the baseline rate of readmission for common pediatric neurosurgical procedures is useful to provide a benchmark for quality improvement efforts.…”
mentioning
confidence: 99%
“…21,24 Other studies reporting on the neurosurgery of the spine show varying results as well. 5,6,25,31,32,36,38 Three studies investigated ASA physical status classification and found it to be significantly elevated in the readmitted group. 21,24,30 Previously, the increasing ASA score has been connected to increased mortality and worse outcomes for several surgical procedures by Wolters et al 39 Comorbid illnesses were also an effective predictor of readmission.…”
mentioning
confidence: 99%